(untitled) (Indus Journal of Bioscience Research, 2025)
Background: "Domestic violence in pregnancy poses a serious public health challenge, leading to substantial risks for both maternal and fetal well-being. Objective: This research was conducted to explore the contributing factors and health-related effects of such violence among pregnant women in interior Sindh, Pakistan, with particular emphasis on emotional, physical, and sexual abuse." Methodology: Study Design: A cross-sectional study. Settings and Duration: This study was conducted at the outpatient department of Peoples University of Medical and Health Sciences for Women (PUMHSW) Hospital, Nawabshah. The study was conducted from July 07, 2023, to January 06, 2024. Sampling Technique: Non-probability consecutive sampling was used to select participants. A total of 120 pregnant women were enrolled in the study. They were asked to complete a structured, pre-validated questionnaire adapted from WHO guidelines. The questionnaire focused on various demographic variables, types of violence, and obstetric outcomes. Data was collected during antenatal visits. After fulfilling the eligibility criteria, participants were selected and examined. The collected data included the presence of domestic violence, the type of violence experienced, obstetric outcomes, and relevant demographic information. The data were analyzed using SPSS version 26, with logistic regression applied to identify predictors of violence and its potential consequences on pregnancy outcomes. Results: Overall, 58.3% of participants reported experiencing some form of domestic violence during pregnancy. Emotional abuse was the most common (85%), followed by sexual (75%) and physical (30%) violence. Significant predictors included illiteracy, husband’s substance abuse, and low socioeconomic status (p<0.05). Adverse outcomes among abused women included anemia, PROM, preterm birth, and low birth weight. Multigenerational impacts were also observed, with behavioral issues reported in children of affected mothers. Conclusion: Domestic violence in pregnancy is highly prevalent in rural Sindh and is associated with both immediate and long-term health risks for mothers and their children. The findings highlight the urgent need for routine screening, preventive education, and culturally tailored intervention programs within antenatal care services. Future research should focus on developing and evaluating community-based strategies to reduce domestic violence and its consequences in resource-limited settings.